2020
DOI: 10.1186/s12955-020-01594-8
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, policy fairness, and subjective life satisfaction of earthquake survivors in Wenchuan, China: a longitudinal study based on post-earthquake survey data

Abstract: Background Existing research has rarely examined an earthquake’s sustained impact and the trajectory of the earthquake survivors’ life satisfaction over time. This study aims to analyze longitudinal changes in life satisfaction of Wenchuan earthquake survivors and the impact of social capital and government relief policy. Methods This research applied a hierarchical linear model to longitudinal survey data collected after the earthqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The necessity of studying the relationship between individual social capital and life satisfaction is mainly considered from the following several aspects. First, previous studies in China either selected specific population as the research object [ 24 , 25 ] or limited study area [ 15 , 26 ]. For example, Pang [ 27 ] investigated the impact of social capital on life satisfaction among Chinese overseas students in Germany and found that social capital is a significant predictor of life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity of studying the relationship between individual social capital and life satisfaction is mainly considered from the following several aspects. First, previous studies in China either selected specific population as the research object [ 24 , 25 ] or limited study area [ 15 , 26 ]. For example, Pang [ 27 ] investigated the impact of social capital on life satisfaction among Chinese overseas students in Germany and found that social capital is a significant predictor of life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The accessibility and applicability of social security are key to upholding social fairness and justice. In particular, the support for disadvantaged groups demonstrates social fairness and justice, which benefits the enhancement of the entire SWB ( Han and Gao, 2020 ; Wang and Li, 2020 ).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Many argued that unfair social distribution and income inequality posed great threats to personal interests, political stability, and social progress, all of which severely decreased people’s happiness and satisfaction, while social fairness was of great benefit to individual happiness ( Huang, 2019 ; Di Martino and Prilleltensky, 2020 ; Roh, 2021 ). Wang and Li (2020) found, for example, that disaster-affected people had a higher fairness perception of government relief policy resulting in life satisfaction of post-disasters if they got satisfactory social security. It is concluded that social security satisfaction may have a positive impact on the realization of social fairness, thereby improving SWB.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…If they get adequate social security, they will have a higher fairness perception of government relief policy resulting in life satisfaction of post-disasters. And fairness moderates the relationship between social capital and changes in life satisfaction among survivors (Liang & Cao, 2015;Wang & Li, 2020). As Amartya Sen said, the root cause of poverty and social inequality is the deprivation of viability, that is, the uneven distribution of rights and benefits (Sen, 1993;Sen, 1999).…”
Section: Social Fairness and Social Trustmentioning
confidence: 99%
“…While, lack of social trust will contribute to conflict and contradiction, economic recession, and poor wellbeing (Suriyanrattakorn & Chang, 2021). It speculates that good social security policies can strengthen individual social trust and thereby promote SWB (Kapteyn & Zamarro, 2013;Wang & Li, 2020). There is still insufficient research on social security, social trust and SWB in China.…”
Section: Social Security Social Trust and Swbmentioning
confidence: 99%